Morbidity and Functional Outcomes Following Rocky Mountain Spotted Fever Hospitalization—Arizona, 2002–2017. (5th October 2022) - Drexler, Naomi A; Close, Ryan; Yaglom, Hayley D; Traeger, Marc; Parker, Kristen; Venkat, Heather; Villarroel, Lisa; Brislan, Jeanette; Pastula, Daniel M; Armstrong, Paige A
Abstract: Background: Rocky Mountain spotted fever (RMSF) is a deadly tickborne disease disproportionately affecting Arizona tribal communities. While the acute clinical effects of RMSF are well-documented, more complete understanding of the long-term health consequences is needed to provide guidance for providers and patients in highly impacted areas. Methods: We performed a retrospective review of hospitalized RMSF cases from 2 tribal communities in Arizona during 2002–2017. Medical records from acute illness were abstracted for information on clinical presentation, treatment, and status at discharge. Surviving patients were interviewed about disease recovery, and patients reporting incomplete recovery were eligible for a neurologic examination. Results: Eighty hospitalized cases of RMSF met our inclusion criteria and were reviewed. Of these, 17 (21%) resulted in a fatal outcome. Among surviving cases who were interviewed, most (62%) reported full recovery, 15 (38%) reported ongoing symptoms or reduced function following RMSF illness, and 9 (23%) had evidence of neurologic sequelae at the time of examination. Sequelae included impaired cognition, weakness, decreased deep tendon reflexes, seizures, and cranial nerve dysfunction. Longer hospitalization (25.5 days vs 6.2 days, P < .001), a higher degree of disability at discharge (median modified Rankin score 1 vs 0, P = .03), and delayed doxycycline administration (6.2 days vs 4.1 days, P = .12) were associated with long-term sequelae by logistic regression. Conclusions: Although the etiology of sequelae is not able to be determined using this study design, life-altering sequelae were common among patients surviving severe RMSF illness. Delayed administration of the antibiotic doxycycline after day 5 was the strongest predictor of morbidity. Abstract : Rocky Mountain spotted fever (RMSF) is a deadly tickborne disease. We identified that 38% of surviving, hospitalized individuals with RMSF reported ongoing symptoms after recovery and 23% had evidence of neurologic sequelae. The presence of sequelae was associated with delayed treatment.